To recruit or to graft? Comparing the recruitment of resident non-neuronal cells by lineage reprogramming with engraftment of stem cell-derived neurons for neuronal replacement therapies - Peterson, Daniel A. (Frontiers in Neuroscience, 2025)
Neurons are post-mitotic cells that are not replaced once lost, leading to the need for neuronal replacement therapies for central nervous system (CNS) repair. The generation of induced pluripotent stem cell (iPSC) derived human neurons is relatively advanced, with the capacity to generate pure and validated populations of different neuronal subtypes as clinical grade cells ready for engraftment. Clinical trials using human-derived embryonic stem cells (hESC) and iPSC-derived neurons are underway. As an alternative approach, the ability to target in vivo resident non-neuronal cells with reprogramming factors to induce replacement neurons has been demonstrated. The ability to engineer a defined population of resident replacement neurons that retain their cytoarchitectural location may permit an additional, more focused therapeutic strategy for specific circuits that could complement the bulk engraftment of ex vivo stem cell-derived replacement neurons. This mini-review summarizes and compares these two strategies and offers a perspective on the steps needed to advance recruitment as a complementary therapeutic strategy.